2019
DOI: 10.18823/asiatefl.2019.16.1.4.53
|View full text |Cite
|
Sign up to set email alerts
|

One, Two, ... , Many : The Outcomes of Paired Peer Assessment, Group Peer Assessment, and Teacher Assessment in EFL Writing

Abstract: The learning potential of pair/team work in language assessment has been demonstrated in the literature, albeit with little concern about challenges faced by the educators to implement it. To contribute to this line of research, the present study aimed to investigate the impact of paired peer assessment, teacher feedback, and group peer assessment on students' writing performance. To do so, 69 second-year university students of the English language were assigned to three classes. The first class received regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 44 publications
0
15
0
1
Order By: Relevance
“…In a more recent study that compared teacher and peer feedback in a college EFL writing classroom, Park (2018) reported that teacher feedback was more favored and incorporated than peer feedback by the students while they still appreciated peer feedback for its own strength. Babaii and Adeh (2019) also compared teacher feedback and two types of peer feedback in an EFL writing class, finding out the greatest performance in the paired peer feedback group.…”
Section: Review Of Previous Studiesmentioning
confidence: 99%
“…In a more recent study that compared teacher and peer feedback in a college EFL writing classroom, Park (2018) reported that teacher feedback was more favored and incorporated than peer feedback by the students while they still appreciated peer feedback for its own strength. Babaii and Adeh (2019) also compared teacher feedback and two types of peer feedback in an EFL writing class, finding out the greatest performance in the paired peer feedback group.…”
Section: Review Of Previous Studiesmentioning
confidence: 99%
“…This finding is in line with earlier studies that highlighted learners' perception of peers as an important factor in peer assessment (cf. Babaii & Adeh, 2019;Ballantyne, Hughes, & Mylonas, 2002;Brown, Irving, Peterson, & Hirschfeld, 2009;Kaufman & Schunn, 2011;Le Hebel et al, 2018;Strijbos, Narciss, & Dünnebier, 2010). More importantly, the findings from the current study indicate how experience and training can contribute to forming the students' beliefs towards mutual trust and consequent learning benefits.…”
Section: Jeongsoon Johmentioning
confidence: 56%
“…Meanwhile, the product of group work was rarely peer-assessed in many of previous PA studies, where pair-work prevailed as the manner of peer assessment, which format is not likely to allow the feedback comments to be shared among all the students in the same classroom. Even when a group work format was employed (e.g., Babaii & Adeh, 2019), the manner was different from in the current study, i.e., only the group leader was given the opportunity to evaluate the members in the group.…”
Section: Jeongsoon Johmentioning
confidence: 95%
See 1 more Smart Citation
“…Reading of the papers excluded seven papers that were reviews (Brown, 2011;Double et al, 2020;McMillan, 2016McMillan, , 2019Van der Kleij & Lipnevich, 2020;Vogl & Pekrun, 2016, Wise & Smith, 2016, five that had no measure of student perceptions of assessment (Babaii & Adeh, 2019;Chen & Lin, 2020;Gordienko, 2015;Natsis et al, 2018;Taghizadeh & Kazemzadeh, 2019), one…”
Section: Methodsmentioning
confidence: 99%